2018
DOI: 10.1038/s41390-018-0135-4
|View full text |Cite
|
Sign up to set email alerts
|

Stoss therapy using fortified biscuit for vitamin D-deficient children: a novel treatment

Abstract: Stoss therapy using fortified biscuit may be an effective way to improve compliance in children who cannot take capsules without adverse effects and may also be recommended for prevention purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 25 publications
(39 reference statements)
0
15
0
Order By: Relevance
“…Screening healthy children for estimating the amount of required vitamin D through medication in addition to sufficient consumption of the nutrients. Finally, countrywide planning for dairy and juice enrichment, and consuming biscuits containing 50000 IU cholecalciferol could also have significant impacts on increasing vitamin D level especially in children (12,(36)(37)(38)(39)(40)(41). A study conducted by Mostafai et al (42) revealed that daily consumption of yogurt fortified with 1000 IU vitamin D for three months could significantly increase serum level of 25(OH) vitamin D by 12.6 ng/dL.…”
Section: Discussionmentioning
confidence: 99%
“…Screening healthy children for estimating the amount of required vitamin D through medication in addition to sufficient consumption of the nutrients. Finally, countrywide planning for dairy and juice enrichment, and consuming biscuits containing 50000 IU cholecalciferol could also have significant impacts on increasing vitamin D level especially in children (12,(36)(37)(38)(39)(40)(41). A study conducted by Mostafai et al (42) revealed that daily consumption of yogurt fortified with 1000 IU vitamin D for three months could significantly increase serum level of 25(OH) vitamin D by 12.6 ng/dL.…”
Section: Discussionmentioning
confidence: 99%
“…The main search resulted in 2063 studies potentially relevant for inclusion ( Figure 1 ); of these, 32 studies 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 (8400 unique participants) met our criteria and were included in this systematic review ( Table 1 ). A subgroup of 21 studies 8 , 9 , 10 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 (7358 unique participants) were eligible for meta-analysis because they included a control group receiving either low-dose vitamin D supplementation (≤400 IU/d) or placebo.…”
Section: Resultsmentioning
confidence: 99%
“…Daily oral high-dose vitamin D intervention ranged from 1200 to 10 000 IU/d, whereas bolus doses ranged from 30 000 IU/week to 600 000 IU as a single dose. Twenty-five of the 32 RCTs 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 26 , 28 , 32 , 33 , 34 , 35 , 36 , 37 had 2 intervention groups, whereas the remaining 7 studies 25 , 27 , 29 , 30 , 31 , 38 , 39 compared more than 2 groups. Only 1 study 11 used 6 years as the upper age limit in their eligibility criteria.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations